La influencia del estilo parental en las intenciones de compra en el consumidor infantil (2019)
This article aims to analyse the relationship between parental style and purchasing intentions in infants, based on aspects such as communication and influ-ence. A quantitative correlational study was carried out with the participation of 90 children living in an intermediate city in Colombia, whose data were processed in the SPSS software. The results of the correlations show that in general the independent variable parental style has a positive relationship with the dependent variable purchase intention of minors. When the analysis is performed exclusively for the authoritarian style, a negative correlation is presented.